Comparative assessment of early mortality risk upon immune checkpoint inhibitors alone or in combination with other agents across solid malignancies: a systematic review and meta-analysis. (December 2022) - Viscardi, Giuseppe; Tralongo, Antonino C.; Massari, Francesco; Lambertini, Matteo; Mollica, Veronica; Rizzo, Alessandro; Comito, Francesca; Di Liello, Raimondo; Alfieri, Salvatore; Imbimbo, Martina; Della Corte, Carminia M.; Morgillo, Floriana; et al.
Abstract: Background: The early crossing of survival curves in randomised clinical trials (RCTs) with immune checkpoint blockers suggests an excess of mortality in the first months of treatment. However, the exact estimation of the early death (ED) rate, the comparison between ED upon immune checkpoint inhibitors (ICI) alone or in combination with other agents and the impact of tumour type, and PD-L1 expression on ED are unknown. Methods: RCTs comparing ICI alone (ICI-only group) or in combination with other non-ICI therapies (ICI-OT group) (experimental arms) versus non-ICI treatments (control arm) were included. ED was defined as death within the first 3 months of treatment. The primary outcome was the comparison of ED between experimental and control arms, and the secondary outcome was the comparison of ED risk between ICI-only and ICI-OT. ED rates estimated by risk ratio (RR) were pooled by random effect model. Results: A total of 56 RCTs (40, 215 participants, 14 cancer types) were included. ED occurred in 14.2% and 6.7% of patients in ICI-only and ICI-OT groups, respectively. ED risk significantly increased with ICI-only (RR: 1.29, 95% CI 1.05–1.57) versus non-ICI therapies, while it was lower with ICI-OT versus non-ICI treatments (RR: 0.81, 95% CI 0.73–0.90). ED risk was significantly higher upon ICI-only compared to ICI-OT (RR: 1.57, 95% CI 1.26–1.95). Gastric and urothelial carcinoma were at higher risk of ED. PD-L1 expression and ICI drug classes were not associated with ED. Conclusions: ED upon first-line ICI is a clinically relevant phenomenon across solid malignancies, not predictable by PD-L1 expression but preventable through the addition of other treatments to ICI. Highlights: This meta-analysis quantifies excess of early mortality upon first-line immunotherapy in solid tumors. Early mortality risk increases with immunotherapy alone versus other treatments. Neither PD-L1 levels nor class of immune checkpoint inhibitors predict early mortality. Gastric and urothelial carcinoma are at higher risk of early mortality upon immunotherapy. Immunotherapy combination strategies can prevent early mortality.